Circular economy approach of enhanced bifunctional catalytic system of CaO/CeO2 for biodiesel production from waste loquat seed oil with life cycle assessment study. (15th May 2021) - Al-Muhtaseb, Ala'a H.; Osman, Ahmed I.; Murphin Kumar, Paskalis Sahaya; Jamil, Farrukh; Al-Haj, Lamya; Al Nabhani, Abdulrahman; Kyaw, Htet Htet; Myint, Myo Tay Zar; Mehta, Neha; Rooney, David W.
Graphical abstract: Highlights: Valorization of sustainable novel waste Loquat Seed Oil into biodiesel fuel. Parametric study revealed that optimum biodiesel yield was 90.14% at short time. Biodiesel yield in reusability without catalyst calcination was reduced by 15%. LCA (midpoint indicators) showed GWP of 1129 kg CO2 eq for entire process for 1000 kg biodiesel. Process is environmentally feasible with net energy ratio as 2.23. Abstract: Herein, we utilised Loquat seed oil as a waste resource to produce biodiesel over a novel bifunctional catalyst system based on CaO loaded on a ceria oxide support. The catalysts were characterised using XRD, SEM-EDX, SBET STEM, and TPD analyses, followed by parametric analysis to optimise the catalyst performance. The XPS analysis showed a strong synergistic effect between CaO and CeO2 support. The parametric study revealed that the most active catalyst (15 wt% CaO-CeO2 ) showed optimum biodiesel yield was 90.14 (±0.1) wt% at a temperature of 70 °C, methanol: oil of 9, time of 90 min and 4 wt% of catalyst. The reusability test showed that when the most active catalyst was calcined and reused, the biodiesel yield was almost the same ±0.5%; however, when biodiesel production was used without calcination, the biodiesel yield was reduced by 15%. The quality of the produced biodiesel was investigated by the American Society for Testing and Materials (ASTM) and European Union (EU) Standards. It showed that it satisfied all standards and could be used as potential alternative fuel instead of fossil diesel from novel Loquat seed oil. The Life cycle Assessment (LCA) was condcuted to assess environmental feasibility of the process with 1000 kg of biodiesel as 1 functional unit (FU). The LCA using midpoint indicators (from CML-IA baseline V3.06 method) showed the cumulative abiotic depletion of fossil resources over the entire process of biodiesel production was 26349 MJ, global warming potential was 1129 kg CO2 eq, and human health toxicity was 422 kg 1, 4-DB eq (kg 1, 4 dichlorobenzene equivalent) per FU. The highest damage in most environmental categories was observed during catalyst preparation and regeneration. This was confirmed in endpoint LCA findings (ReCiPe 2016 Endpoint (E) V1.04), where catalyst preparation contributed to human health (119.2 Point (Pt)), ecosystems damage (9.3 Pt) and resources depletion (0.5 Pt). Furthermore, the net energy ratio was 2.23 for the biodiesel production process (computed as output energy/input energy) by considering allocation of output energy due to biodiesel and glycerol.